Senyuman untuk Lansia di Masa Pandemi - Maya Khairani; Samia Sakinah Mahdi; Syarifa Nessa; Rachmad Farazi; Trivia Febriyanti (Faculty of Ushuluddin and Humanities, 2022)
The COVID-19 pandemic demands everyone to adjust with new customs in everyday life. The implementation of social distancing has been an issue on it’s own for the elderly. Those who have to live separately from their families become further isolated due to these regulations. Psychological issues have began to emerge in the elderly such as feelings of loneliness, sadness from not being able to meet grandchildren, fear, anxiety, feelings of worry, etc. Responding to these issues, a video entitled “Senyuman untuk Lansia” or “A Smile for the Elderly” was created to give encouragement to the elderly. 32 respondents (Mage = 66,02) partcipated in a survey to give their impression of the video. There are four major themes gathered from the surve, namely the impression, positive emotions, negative emotions, and hopes or expectations that arised after watching the video.